Special Topic: Quantum sensing with correlated light sources - Clark, Alex S.; Chekhova, Maria V.; Matthews, Jonathan C. F.; Rarity, John G.; Oulton, Rupert F. (Applied Physics Letters, 2021)
The quantum revolution of the 20th century has culminated in the development of quantum optics and the study of nonclassical light. A major milestone for quantum sensing is its application to new disciplines, which has been showcased by the next-generation of gravitational-wave detectors that employ squeezed light to enhance detector sensitivity. Quantum optical sensing relies on sources of correlated photon pairs or bright twin beams, produced by spontaneous parametric down-conversion (SPDC). The Setzpfandt group report on the use of SPDC to perform ghost imaging using a pinhole to form an image, removing the need for lenses in imaging, is discussed. The group has also highlighted the utility of their tunable photon-pair source for quantum enhanced spectroscopy.
CRIS-Team Scopus Importer:2023-03-27